Second annual report of the Hospital for Natural Healing : 1936-7 - Hospital for Natural Healing (London, England) (1937)
1937 1937 1930s 13 pages [photograph] [photograph] Patient undergoing examination in Nose and Throat Dept. [photograph] Patient in Consulting Room. 292/842/2/237